1976
DOI: 10.1111/j.1651-2227.1976.tb04411.x
|View full text |Cite
|
Sign up to set email alerts
|

The Periurethral Aerobic Flora in Girls Highly Susceptible to Urinary Infections

Abstract: After the age of 5 years, normal children have but few aerobic gram-negative rods periurethrally. This study examines whether there is an abnormal periurethral colonization in urinary tract infection-prone girls during infection-free intervals, indicating a defective local defence. In 13 girls with a history of recurrent infection, daily bacterial samples were obtained from the periurethral area and from urine. Sampling continued until an infection eventually occurred. Seven girls contracted a urinary tract in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
5

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(33 citation statements)
references
References 16 publications
2
26
0
5
Order By: Relevance
“…The infecting E. coli type can often be isolated from the faeces before or at onset of symptomatic UTI (Griineberg, Leigh & Brumfitt, 1968;Lidin-Janson et al 1977), and it has furthermore been shown that colonization of the vaginal introitus and the periurethral area precedes the infection (Cooke & Ewins, 1975;Bollgren & Winberg, 1976;Fowler & Stamey, 1977).…”
Section: Urinary Tract Infections (Uti)mentioning
confidence: 99%
“…The infecting E. coli type can often be isolated from the faeces before or at onset of symptomatic UTI (Griineberg, Leigh & Brumfitt, 1968;Lidin-Janson et al 1977), and it has furthermore been shown that colonization of the vaginal introitus and the periurethral area precedes the infection (Cooke & Ewins, 1975;Bollgren & Winberg, 1976;Fowler & Stamey, 1977).…”
Section: Urinary Tract Infections (Uti)mentioning
confidence: 99%
“…Although the healthy vagina is infrequently colonized by members of the family Enterobacteriaceae, colonization of the vaginal introitus with E. coli usually precedes acute cystitis (2,7,13 for only a few antibiotics (4,5,11,14). Moreover, the influence of the new fluorinated quinolone antibiotics, such as ofloxacin, on vaginal colonization with E. coli has not been previously reported.…”
Section: Discussionmentioning
confidence: 97%
“…Vaginal colonization with Escherichia coli is an integral first step in the pathogenesis of acute cystitis, and persistent vaginal colonization with E. coli has been associated with the development of recurrent urinary infections in women (2,7,13). However, few studies have examined the pharmacodynamic properties of antibiotics in vaginal fluid or their effect on vaginal E. coli colonization.…”
mentioning
confidence: 99%
See 2 more Smart Citations